Endoscopic pilonidal sinus treatment: a prospective multicentre trial. (May 2016) - Meinero, P.; Stazi, A.; Carbone, A.; Fasolini, F.; Regusci, L.; La Torre, M.
Abstract: Background: Pilonidal disease (PD) is a common inflammatory disease of the gluteal fold, resulting in recurrent acute/chronic infection at the level of the natal cleft. In this study, endoscopic pilonidal sinus treatment (EPSiT), a new endoscopic minimally invasive procedure, was evaluated for its effectiveness in treating PD. Methods: Two hundred and fifty prospective patients with chronic PD were enrolled in a prospective multicentre study conducted at a secondary and tertiary colorectal surgery centre. The primary end‐point of this study was wound healing, and the short‐/long‐term outcomes such as healing time, morbidity rate and recurrence rate were analysed. The secondary end‐point of this study was quality of life (QoL). Results: The complete wound healing rate was 94.8%, and the mean complete wound healing time was 26.7 ± 10.4 days. The incomplete healing rate (5.2%) was significantly related to the number of external openings ( P  =   0.01). There was no difference in the failure rate when EPSiT was performed as the first‐line treatment for PD or when it was used after unsuccessful procedures ( P  = n.s.). Recurrence occurred in 12 cases (5%). The QoL significantly increased from preoperative levels 15 days after the EPSiT procedure (45.3 vs 7.9; P  <   0.0001). Conclusions: The EPSiT procedure is a safe and effective technique for treating PD. It provides better short‐ and long‐term outcomes than various other techniques that are more invasive. EPSiT is a minimally invasive outpatient procedure, which is associated with a quick recovery and a good QoL outcome.